# 15pq-6p+5q-2

Please find below the solution to the asked query :

$15\mathrm{pq}-6\mathrm{p}+5\mathrm{q}-2\phantom{\rule{0ex}{0ex}}=3\mathrm{p}\left(5\mathrm{q}-2\right)+1\left(5\mathrm{q}-2\right)\phantom{\rule{0ex}{0ex}}=\left(3\mathrm{p}+1\right)\left(5\mathrm{q}-2\right)\mathrm{ANS}...$

$15\mathrm{pq}-6\mathrm{p}+5\mathrm{q}-2\phantom{\rule{0ex}{0ex}}=3\mathrm{p}\left(5\mathrm{q}-2\right)+1\left(5\mathrm{q}-2\right)\phantom{\rule{0ex}{0ex}}=\left(3\mathrm{p}+1\right)\left(5\mathrm{q}-2\right)\mathrm{ANS}...$

Regards

**
**